A Project by Giacomo Quarenghi for the renovation of a large building - Piervaleriano Angelini (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2023)
In a private Italian collection, a drawing with the plan of a very large building has been identified containing some ideas for the partial transformation of the building. The owner of this building is not known, nor is the location of the building, but analysis of the architectural renovation of the northern part of the building, and of the graphic style and calligraphic evidence may indicate the Italian architect Giacomo Quarenghi as its author, and therefore Russia as the country it was drawn up for.